HRM IN THE METAVERSE: VIRTUAL REALITY WORKSPACES AND THEIR IMPLICATIONS FOR ORGANIZATIONAL CULTURE - Sari Mariahma Nova Sipayung; Rustiyana Rustiyana; Dyah Maharani (ADISAM Publisher, 2026)
The development of digital technology has encouraged organizations to adopt the metaverse as a virtual reality-based workspace that offers immersive and collaborative work experiences. This transformation has significant implications for Human Resource Management (HRM) practices, particularly in human resource management, work interaction patterns, and the formation and maintenance of organizational culture. This research aims to comprehensively examine the role of HRM in the metaverse context and analyze the implications of virtual workspace use on organizational culture. The method used is a literature review, examining various scientific sources, including journal articles, academic books, and relevant publications discussing the metaverse, virtual reality, digital HRM, and organizational culture. The results indicate that implementing the metaverse in the workplace has the potential to change communication dynamics, organizational values, employee engagement, and leadership practices and collaboration across geographic boundaries. Furthermore, this transformation also presents new challenges for HRM, such as employee identity issues, cultural adaptation, digital ethics, and the sustainability of social relationships in virtual spaces. This research is expected to provide theoretical contributions to the development of digital HRM studies and serve as a practical reference for organizations in designing human resource management strategies that are adaptive to metaverse-based work ecosystems.